Maintaining a Reputation Against a Long-Lived Opponent - Celetani, Marco; Fudenberg, Drew; Levine, David K.; Pesendorfer, Wolfgang (Econometrica, 1996)
4 Celentani (1996) uses multiple types of short-run players to get around the problem of unobservable off-path behavior of the long-run player in repeated games with observable actions.His approach can be extended to short run players who live for more than one periodo